Diseño de un manual de procedimientos y procesos de crédito y cobranzas de la Empresa In.Telnet S.A.S. - Barreto Herrera, Concepción Doménica (2024)
This research paper discusses the design of a procedures and processes manual for credit and collections within the company In.Telnet S.A.S. The management of overdue accounts is very important, as inadequate management and lack of follow-up can compromise the economic and financial stability of the entity. Throughout the research process, many strategies were implemented. One of the most significant findings was that the personnel working in the credit and collections area were surveyed. They expressed their interest in the proposal from the collaborators to create a collections policy manual and a new collections department within the entity. These collaborators indicated that such a manual and a new collections department would be of great help in improving communication with customers who have overdue debts. Likewise, a survey tool was applied, duly considering the partners in the credit and collections area. The recommendation of this research is to develop a credit policies and procedures manual aimed at reducing overdue accounts. This manual should clearly articulate specific steps to enable the personnel within the areas to carry out activities optimally.